Variations in Pancreatic Duct Course, Configuration and Pancreaticobiliary Junction on MRCP in 3-T MRI: A Descriptive Cross Sectional Study - Jha, Anamika; Tuladhar, Sasmita; Jha, Sujit K; Gurung, Ghanshyam; Karki, Dan B (Journal of Institute of Medicine Nepal, 2022)
Introduction Anomalies and anatomic variations of the pancreatic duct must be identified because they can predispose to conditions like pancreatitis, choledochal cysts, and cholangiocarcinoma, as well as increase surgical complications. In this study, we describe the course and configuration of pancreatic ducts and pancreaticobiliary confluence in cholangiopancreaticography on 3-Tesla magnetic resonance (3-T MR) scanner. Methods This cross-sectional descriptive study was done after obtaining ethical clearance, and included 128 magnetic resonance cholangiopancreatography (MRCP). The MRCP image records from December 2015 to 2018 were retrospectively analyzed for pancreatic duct course, configuration, angle of pancreaticobiliary confluence and common channel. Obtained data was entered in previously prepared proforma. Statistical analysis was performed using SPSS v 16. Results There were 56 (43.8%) males and 72 (56.2 %) females with mean age 48.72±18.05 years, ranging from 3 - 84 years. The most common pancreatic duct course was descending in 45 (36.3%) followed by sigmoid in 42 (33.9%) and vertical in remaining 37 (29.8%) patients. The most common ductal configuration was rudimentary non-dominant duct of Santorini in 88 (71%) patients followed by bifid configuration with dominant duct of Wirsung in 27 patients (21.8%). Pancreatico-biliary junction was more often acute angled than right or obtuse. The common indications for undergoing MRCP were pain abdomen (102, 82.8%), vomiting (53, 43%) and jaundice (36, 28.9%). Conclusion In symptomatic patients undergoing MRCP, the common anomalies of the pancreatic duct observed were descending course, rudimentary non-dominant duct of Santorini configuration and acute pancreatico-biliary angle.